2021
DOI: 10.1002/jssc.202100730
|View full text |Cite
|
Sign up to set email alerts
|

Determination of multiple antibiotics in agricultural soil using a quick, easy, cheap, effective, rugged, and safe method coupled with ultra‐high performance liquid chromatography‐tandem mass spectrometry

Abstract: In this study, we combined ultra-high performance liquid chromatography with tandem mass spectrometry to establish a quick, easy, cheap, effective, rugged, and safe method of detecting 21 target antibiotics in agricultural soil samples.Antibiotics were extracted with mixed solvents consisting of ethylenediaminetetraacetic acid disodium salt dihydrate and phosphoric acid citric acid buffer and acetonitrile which were purified with octadecylsilyl as an adsorbent and anhydrous sodium sulfate as a desiccant. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Currently, several approaches have been developed for the detection of antibiotics, such as the enzyme-linked immunosorbent assay (ELISA), 8 Raman spectroscopy, 9 surface plasmon resonance (SPR) sensors, 10 fluorometric detection, 11 high-performance liquid chromatography (HPLC), 12 capillary electrophoresis, 13 colorimetric sensors, 14 and electrochemical detection. 15 Nonetheless, while most of these conventional techniques offer high sensitivity and accuracy, they can only be performed in well-equipped laboratories by trained personnel.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several approaches have been developed for the detection of antibiotics, such as the enzyme-linked immunosorbent assay (ELISA), 8 Raman spectroscopy, 9 surface plasmon resonance (SPR) sensors, 10 fluorometric detection, 11 high-performance liquid chromatography (HPLC), 12 capillary electrophoresis, 13 colorimetric sensors, 14 and electrochemical detection. 15 Nonetheless, while most of these conventional techniques offer high sensitivity and accuracy, they can only be performed in well-equipped laboratories by trained personnel.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an effective clean-up step is needed to remove these high solubility impurities [18]. A series of cleanup sorbents including graphitized carbon black, N-octadecylsilane (C18), primary secondary amine, and carbon nanotubes (CNTs) have been investigated in QuEChERS methods for the removal of various impurities such as sugar, fat, lipids and pigments [19][20][21]. Multiwall CNTs (MWCNTs) and their derivatives with numerous hydroxyl groups, unique structure, large surface area, and ease of modification are especially attractive sorbents in the modified QuEChERS methods for the detection of pesticides in complex processed foods such as canned fruit [22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been found that antibiotics can cause mitochondrial proteotoxic stress and alter chloroplast function, gene expression, and cell proliferation [8]. Antibiotic concentrations in agricultural soils may also disturb germination, diminish biomass, and consequently lower production in farms fertilized with contaminated manure [9,10]. Furthermore, antibiotic residues can affect the human microbiota and produce health problems such as allergic reactions, persistent toxic effects after long-term exposure, and digestive system disturbance [10,11].…”
Section: Introductionmentioning
confidence: 99%